Hackathon CCAFS COP20 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Latin American and Carribean hackers design innovative solutions to feed the world in a changing climate during a Hackathon on the sidelines of the 20th Conference of the Parties (COP20) in Lima, Peru, November 2014. For more information visit https://ccafs.cgiar.org/news/hackers-design-innovative-solutions-feed-world-changing-climate The event was organised by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), with support from the CGIAR Consortium, and the Technical Centre for Agricultural and Rural Cooperation (CTA).